2019
DOI: 10.1038/s41419-019-1838-0
|View full text |Cite|
|
Sign up to set email alerts
|

The Hippo effector TAZ promotes cancer stemness by transcriptional activation of SOX2 in head neck squamous cell carcinoma

Abstract: The Hippo-TAZ signaling has emerged as a fundamental regulator underlying cancer stem cells (CSCs) stemness which intricately associates with local recurrence and metastatic spreading in head neck squamous cell carcinoma (HNSCC). However, the precise downstream targets of TAZ responsible for HNSCC CSCs maintenance remain largely underexplored. Here, we identified Sex determining region Y box 2 (SOX2) as a putative downstream target of TAZ to promote CSCs maintenance and tumorigenicity in HNSCC. Both TAZ and SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 49 publications
(82 reference statements)
1
40
0
2
Order By: Relevance
“…63 The TEAD4-TAZ complex can also bind to the promoter of SOX2 and modulate cancer stem cell selfrenewal in head-neck squamous cell carcinoma. 38 Consistent with the findings above, TEAD4-induced metastasis is common in gastric cancer, 36 breast cancer, 48 lung cancer, 42 and colorectal cancer. 11 This is plausible as cancer cells that undergo EMT detach, traverse the basement membrane, enter the bloodstream, and disseminate elsewhere for metastatic colonization.…”
Section: Functional Role Of Tead4 In Cancersupporting
confidence: 85%
“…63 The TEAD4-TAZ complex can also bind to the promoter of SOX2 and modulate cancer stem cell selfrenewal in head-neck squamous cell carcinoma. 38 Consistent with the findings above, TEAD4-induced metastasis is common in gastric cancer, 36 breast cancer, 48 lung cancer, 42 and colorectal cancer. 11 This is plausible as cancer cells that undergo EMT detach, traverse the basement membrane, enter the bloodstream, and disseminate elsewhere for metastatic colonization.…”
Section: Functional Role Of Tead4 In Cancersupporting
confidence: 85%
“…Further, the activation of the PI3K through mitogenic signaling inhibits the Hippo pathway leading to YAP1 activation and cell growth ( Fan et al, 2013 ). On the other hand, WWTR1 was shown to act upstream of SOX2, facilitating stemnesses in HNSCC ( Li et al, 2019 ). Intriguingly, while WWTR1 knockdown led to reduction of SOX2 mRNA and protein expression, this was not seen when YAP1 was knockdown in the HNSCC cells (Cal27 and Fadu) ( Li et al, 2019 ; Huang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, WWTR1 was shown to act upstream of SOX2, facilitating stemnesses in HNSCC ( Li et al, 2019 ). Intriguingly, while WWTR1 knockdown led to reduction of SOX2 mRNA and protein expression, this was not seen when YAP1 was knockdown in the HNSCC cells (Cal27 and Fadu) ( Li et al, 2019 ; Huang et al, 2017 ). In support of that, an inverse relationship between the expression levels of YAP1 and ΔNp63 were reported in lung SCC tumor samples ( Huang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we characterised for the first time CSCs in populations of primary OSCC cells using CD133. Other studies suggest that SOX2 is critically involved, at least in part, in cancer initiation and progression via modulation of CSC stemness 39 . Moreover, a review indicated that NANOG, ALDH1A1, and OCT4 could serve as CSC markers and were predictive of poor prognosis 40 .…”
Section: Discussionmentioning
confidence: 99%